Effect of Piperine on Cypermethrin-Induced Genotoxicity in Wistar Rats - Sankar, Palanisamy; Telang, Avinash G; Ramya, Kalaivanan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The indiscriminate use of cypermethrin, a type II pyrethorid to enhance crop production has aroused great concern, because this products is likely to reach the aquatic environment, thereby posing a health concern for humans and animals. The aim of the present study was to investigate the protective effect of piperine on cypermethrin-induced genotoxicity in rats. The rats were divided into five groups of six each.  Group I was kept as the control and group II was used as vehicle control. Groups III, IV and V were administered orally with cypermethrin (25 mgkg body wt), piperine (50mg kg body wt) and both daily for 4 weeks, respectively. Administration of cypermethrin (25 mg/kg, p.o.) for 28 days resulted in significant increase in the frequency of micronuclei formation in bone marrow cells and DNA damage. piperine (50 mg/kg, p.o.) administration caused significant reduction in micronuclei formation and marked reduction in DNA damage. The present study revealed that presence of piperine could reduce cypermethrin-induced genotoxicity in rats.
Keywords: Comet assay; Cypermethrin; Genotoxicity; Piperine; Rats